2010
DOI: 10.3198/jpr2009.07.0392crg
|View full text |Cite
|
Sign up to set email alerts
|

Registration of Arblick and Ecoturf Rhizoma Peanut Germplasms for Ornamental or Forage Use

Abstract: Arblick (Reg. No. GP‐128; PI 658528) and Ecoturf (Reg. No. GP‐129; PI 658529) are rhizoma peanut (RP) (Arachis glabrata Benth.) germplasms released by the Univ. of Florida in 2008. These plant introductions were identified as lower growing “ground cover” type plants. These lines are being released as germplasm to document the dual purpose ornamental and forage characteristics of the lines. Arblick was collected near the town of Bela Vista, Brazil, located on the border of Brazil and Paraguay. It has green grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
31
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 4 publications
1
31
0
Order By: Relevance
“…'Ecoturf' and 'Arblick' were released as cultivars for landscapes by Prine et al (2010) and are used as a groundcover along highways, landscape berms, road medians, and in plantations for soil preservation (Mathews et al, 2000;Hernandez-Garay et al, 2004). The situation significantly changed when a series of major collection expeditions were made to Bolivia, Brazil, Paraguay, and northern Argentina beginning in diseases and nematodes common to peanut, is drought tolerant, and has minimal fertilizer requirements.…”
Section: Species Of Arachismentioning
confidence: 99%
“…'Ecoturf' and 'Arblick' were released as cultivars for landscapes by Prine et al (2010) and are used as a groundcover along highways, landscape berms, road medians, and in plantations for soil preservation (Mathews et al, 2000;Hernandez-Garay et al, 2004). The situation significantly changed when a series of major collection expeditions were made to Bolivia, Brazil, Paraguay, and northern Argentina beginning in diseases and nematodes common to peanut, is drought tolerant, and has minimal fertilizer requirements.…”
Section: Species Of Arachismentioning
confidence: 99%
“…Several new genotypes of RP have been developed and released as dual-purpose hay and grazing crops, ranging in growth habit from decumbent-to upright-growing types Quesenberry et al, 2010). It was released as a germplasm by Prine et al (2010), and evaluation under grazing in small plots showed no difference in herbage accumulation (HA) between Ecoturf and cultivars 'Florigraze', 'UF-Tito', and 'UF-Peace' (Mullenix et al, 2016a). It was released as a germplasm by Prine et al (2010), and evaluation under grazing in small plots showed no difference in herbage accumulation (HA) between Ecoturf and cultivars 'Florigraze', 'UF-Tito', and 'UF-Peace' (Mullenix et al, 2016a).…”
mentioning
confidence: 99%
“…Because RP is a long-lived perennial with ability to move laterally via an extensive rhizome system, it has potential to spread into the surrounding grass sward over time and form a mixed pasture. Prine et al (2010) also released the germplasms Ecoturf and Arblick as low-growing ecotypes for grazing or ornamental use. There are other recently released cultivars and genotypes of RP that may have potential for incorporation into existing grass pastures, but they have not been tested.…”
mentioning
confidence: 99%